Xanthones from the Pericarp of Garcinia mangostana - Yang, Renyue (Molecules, 2017)
Mangosteen (Garcinia mangostana L.) is one of the most popular tropical fruits (called the “Queen of Fruits”), and is a rich source of oxygenated and prenylated xanthone derivatives. In the present work, phytochemical investigation has resulted in one new prenylated xanthone and 13 known xanthones isolated from the pericarp of G. mangostana. Their structures were established by spectroscopic data analysis, including X-ray diffraction. The new one was further tested for cytotoxic activity against seven cancer cell lines (CNE-1, CNE-2, A549, H490, PC-3, SGC-7901, U87), displaying the half maximal inhibitory concentration (IC(50)) values 3.35, 4.01, 4.84, 7.84, 6.21, 8.09, and 6.39 μM, respectively. It is noteworthy that the new compound can promote CNE-2 cells apoptosis in late stage, having a remarkable inhibition effect on the side population growth of CNE-2 at 1.26 μM. The bioactive compound was also detected in extract from fresh mangosteen flesh, which indicated that the popular fruit could have potential cytotoxic activity for cancer cell lines.